2006
DOI: 10.1021/bi060264j
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Heat Shock Proteins on Cancer Cells:  Selection, Characterization, and Cell-Penetrating Properties of a Peptidic GRP78 Ligand

Abstract: Peptidic ligands can be used for specific cell targeting and the delivery of payloads into the target cell. Here we describe the screening of a pool of cyclic peptide phage display libraries using whole-cell panning against human melanoma cell line Me6652/4. This strategy resulted in the selection of the cyclic 13-mer Pep42, CTVALPGGYVRVC, which showed preferential internalization into melanoma cell line Me6652/4 versus the reference cell line Me6652/56. This translocation is a receptor-mediated process that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
166
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(172 citation statements)
references
References 48 publications
5
166
0
1
Order By: Relevance
“…Previous studies using transmembrane prediction programs have suggested that GRP78 has four potential transmembrane domains at the cell surface: I (amino acids (aa) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], II (aa 29 -45), III (aa 222-242), and IV (aa 414 -431) (34). However, the studies performed here demonstrate that at least residues 416 -417 are exposed on the cell surface, as this is the sole SubA cleavage site, and we observe cell-surface cleavage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using transmembrane prediction programs have suggested that GRP78 has four potential transmembrane domains at the cell surface: I (amino acids (aa) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], II (aa 29 -45), III (aa 222-242), and IV (aa 414 -431) (34). However, the studies performed here demonstrate that at least residues 416 -417 are exposed on the cell surface, as this is the sole SubA cleavage site, and we observe cell-surface cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…GRP78 at the cell surface is detected in multiple types of cancer cells both in vitro and in vivo and is usually not present on non-malignant cells (9,10). Furthermore, the expression of GRP78 on the cell surface is associated with tumor progression, metastasis, and a poor prognosis (11).…”
mentioning
confidence: 99%
“…Additional proteins with ER retention signals are also detected extracellularly, including GRP78 (BiP) and GRP94 (Hsp90␤), and there is evidence for the function of these proteins in the extracellular space. For example, GRP78 was first identified at the surface of malignant lymphocytes (17), and the elevated levels observed on the surface of malignant cells have been exploited to successfully target and kill these cells with small molecules (18,19). GRP94 is similarly detected at the membrane in the nervous system, where it was found to regulate cell migration (20).…”
mentioning
confidence: 99%
“…A search of present literature published between 2005 and 2006 revealed > 30 papers that disclose the identification of peptides using phage display, which were demonstrated to specifically target proteins in vitro. The technology has been used in attempts to develop novel targeting therapeutics or diagnostic reagents for human cancers [23,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], HIV infection [59,60], human papilloma virus infection [61], obesity [62], bacterial infection [63][64][65][66], parasitic infection [67], autoimmune disorders [68], thrombosis and inflammation [69,70], Alzheimer's disease [71] and increasing vaccine efficacy [72]. However, the in vivo therapeutic efficacy of these novel peptides remains to be determined.…”
Section: Potential Target-specific Peptides Identified Using Phage-dimentioning
confidence: 99%